Conceptual Framework and Development of Quality Management for Islamic Higher Education in Indonesia - Khairul Azan; Kemas Imron Rosadi; Muntholib Muntholib (Indonesian Academy of Social and Religious Research (IASRR), 2021)
Quality is a determining indicator of the existence of Islamic higher education institutions in the future. Higher education with quality will be in demand by the community. Therefore, quality must be a priority indicator in the implementation of Islamic-based higher education. In order for the quality to continue to increase, universities should implement the concept of Total Quality Management (TQM) in all areas of university administration. Integrated quality management requires the existence of an Internal Quality Assurance System (SPMI) which aims to ensure the implementation of ducation according to standards. In order for the Internal Quality Assurance System (SPMI) to run well, it is necessary to have a quality culture that is well understood and implemented by stakeholders. The quality culture contains several aspects, namely: 1) focus on customers, 2) obsession with quality, 3) scientific approach, 4) long-term commitment, 5) teamwork, 6) continuous improvement of the system, 7) education and training, 8) controlled freedom, 9) respect for everyone, 10) unity of purpose, 11) involvement and empowerment of employees. Efforts that can be made in developing and maintaining the quality of Islamic higher education include: 1) Strategic Plan as a basis for implementing education, 2) building a higher education brand image, 3) consistency in implementing the internal quality assurance system.